AB0270 Worsening of Diagnostic Delay in Early Arthritis during The Last 10 Years: A Single Center Experience. (15th July 2016) - Benaglio, F.; Bugatti, S.; Crepaldi, G.; Sakellariou, G.; Montecucco, C.; Caporali, R.
Abstract : Background: The reduction of the diagnostic delay in patients with early arthritis, in order to start treatment as early as possible and to improve outcomes, has required a considerable effort during the last 15 years. Objectives: To evaluate the diagnostic delay, between 2004 and 2015, at our Early Arthritis Clinic (EAC). Methods: 943 patients with rheumatoid arthritis (RA) (according to 1987 and/or 2010 classification criteria) or undifferentiated arthritis (UA) evaluated at our EAC between September 2004 to September 2015 were recruited (disease duration <12 months) and divided into 2 groups according to the time of diagnosis (group 1: 2004–2009; group 2: 2010–2015). A comparison among demographic features, diagnostic delay and disease activity (DAS28) at first evaluation was performed. Results: A total of 943 patients were evaluated: 469 patients into the group 1 (74.4% women, mean age 58 ys) vs. 474 patients into the group 2 (74.7% women, mean age 57 ys). No differences were found in terms of serologic positivity and diagnosis. At baseline, patients in the group 2 showed lower disease activity as for DAS28 (4.86±1.17 vs. 4.32±1.24; p=0.0001), number of tender joints (6 IQR 2–11 vs. 4 IQR 2–8; p=0.0001), swollen joints (6 IQR 4–11 vs. 4 IQR 2–7; p=0.0001), ESR (22 IQR 13–40 vs. 16, 5 IQR 8–33; p=0.0001). In contrast, patients in the group 1 showed lower time from the onset of symptoms to the diagnosis (111 days IQR 67–200 vs. 129 IQR 77–228; p=0.008). Data about the diagnostic delay comparing DAS28 categories are showed in figure 1 : particularly in the group 2 there was a reduction in the number of patients in high disease activity-DAS28 who have the diagnosis established within the first 90 days after the onset of the disease (p=0, 0026). 40% of patients in group 1 vs. 31% in group 2 had the diagnosis established within 90 days (p=0.005); however, the delay from the referral to the first evaluation at our EAC was similar in the two groups (21 days IQR 12–31 vs. 21 IQR 14–29; p=ns). Conclusions: Currently, about 70% of the diagnosis is still not made within the so-called window of opportunity (90 days from the onset of symptoms). Moreover, a slight but significant worsening in the diagnostic delay has been observed; the delay doesn't seem to be related neither with time elapsing from referral to the first evaluation at the EAC nor to a lower disease activity at the beginning. Education programs at patients' and general practitioners' level should be implemented in order to reduce the delay and further improve the outcome. References: Nell VP, et al. Benefit of very early referral and very early therapy with disease-modifying anti-rheumatic drugs in patients with early rheumatoid arthritis. Rheumatology 2004;43:906–14. Van der Linden MP, et al. Long-term impact of delay in assessment of patients with early arthritis. Arthritis Rheum. 2010;62:3537–46. Disclosure of Interest: None declared